The Influence Of Word Of Mouth And Brand Image On Purchasing Decisions In Make Over Cosmetics (Survei of Make Over Consumers in Tasikmalaya City) - Heryani, Rena; Yusnita, Rita Tri; Barlian, Barin (Journal of Management, Economic, and Accounting, 2024)
This research aims to determine the simultaneous and partial influence of word of mouth and brand image on purchasing decisions for Make Over cosmetic products. The research method used in this research is a quantitative research method with a survei approach. The sampling technique used was incidental sampling and the sample taken was 100 respondents. The analytical tool used is the multiple regression equation. The research results show that word of mouth and brand image simultaneously have a significant influence on purchasing decisions for Make Over cosmetic products. Word of mouth partially has a significant influence on purchasing decisions for Make Over cosmetic products. Brand image partially has a significant influence on purchasing decisions for Make Over cosmetic products.